Production patterns of loblolly pine plantations along a geographic gradient in southern Brazil - Munhoz, Juliana Soares Biruel; Alvares, Clayton Alcarde [UNESP]; Carneiro, Rafaela Lorenzato; Kulmann, Matheus Severo de Souza; Stape, José Luiz [UNESP] (Elsevier, 2024)
Pinus taeda plantations depend directly on the supply of resources (light, water, and nutrients) available to the stand. However, studies quantifying edaphic and climatic factors in P. taeda stands are scarce. This study aimed to identify the main edaphic, climatic and stand factors that influence the productivity and growth pattern of P. taeda plantations in southern Brazil. A total of 24 stands, ranging between 8 and 10 years old were evaluated. Biometric variables such as height, diameter at breast height (DBH), stem analysis, growth rings, specific gravity, and soil chemical and physical variables were evaluated. Site index (SI), stem biomass, mean annual increment without bark (MAI) and correlations between variables were calculated. We observed that by nine years after planting, none of the plots had reached their maximum growth; and MAI, standing stem biomass and SI ranged from 15 to 35 m³ ha−1 year−1, 56–131 Mg ha−1, and 12–19 m, respectively, with higher values in Três Barras site. Stem biomass were positively related with SI (r = 0.89), and stem production was related with higher available water content (r = 0.41), warm temperatures (r = 0.61), and higher relative air humidity (r = 0.58). The study corroborates the role of nutrients, well-drained soils, mild climatic conditions, and low water deficit to explain the high yields of P. taeda in Brazil compared to other locations around the world. Based on these results, studies on fertilization, genetic material, and more frequent use of stem analysis, associated with X-ray densitometry, are recommended for P. taeda.
Keywords: Climatic effect; Edaphic effect; Growth ring analyses; Pinus taeda; Productivity